Zn(Cu)Si2+xP3 Solid Solution Anodes for High‐Performance Li‐Ion Batteries with Tunable Working Potentials. (18th June 2019) - Li, Wenwu; Liao, Jun; Li, Xinwei; Zhang, Lei; Zhao, Bote; Chen, Yu; Zhou, Yucun; Guo, Zaiping; Liu, Meilin
Abstract: Si‐based anodes with a stiff diamond structure usually suffer from sluggish lithiation/delithiation reaction due to low Li‐ion and electronic conductivity. Here, a novel ternary compound ZnSi2 P3 with a cation‐disordered sphalerite structure, prepared by a facile mechanochemical method, is reported, demonstrating faster Li‐ion and electron transport and greater tolerance to volume change during cycling than the existing Si‐based anodes. A composite electrode consisting of ZnSi2 P3 and carbon achieves a high initial Coulombic efficiency (92%) and excellent rate capability (950 mAh g −1 at 10 A g −1 ) while maintaining superior cycling stability (1955 mAh g −1 after 500 cycles at 300 mA g −1 ), surpassing the performance of most Si‐ and P‐based anodes ever reported. The remarkable electrochemical performance is attributed to the sphalerite structure that allows fast ion and electron transport and the reversible Li‐storage mechanism involving intercalation and conversion reactions. Moreover, the cation‐disordered sphalerite structure is flexible to ionic substitutions, allowing extension to a family of Zn(Cu)Si2+ x P3 solid solution anodes ( x = 0, 2, 5, 10) with large capacity, high initial Coulombic efficiency, and tunable working potentials, representing attractive anode candidates for next‐generation, high‐performance, and low‐cost Li‐ion batteries. Abstract : Compared with Si, the novel cation‐disordered ZnSi2 P3 shows faster electron, Li‐ion transportation capability and better resistance to volume change, thus delivering better Li‐storage performance. Moreover, this specific case can be further extended to a novel family of Zn(Cu)Si2+ x P3 with adjustable working potentials by cationic substitution of Cu and solid solution with more Si.